Classification model of optical character recognition failures in unrecovered slider serial numbers in hard disk drive manufacturing and image capture processes - Chousangsuntorn, Chousak; Tongloy, Teerawat; Chuwongin, Santhad; Boonsang, Siridech (My University, 2022)
In hard disk drive (HDD) manufacturing processes, there are unrecovered serial number images about 0.01% from the standard optical character recognition (OCR) reading and deep learning approach. We found several failures from two main causes, i.e. manufacturing process and image capture process during standard OCR reading. We proposed classification model used for recognizing the serial number reading failures based on object detection You-Only-Look- Once (YOLO) algorithm and EfficientNet-B0 classification network as well as histogram analysis. The 1000 images captured by digital camera were used for training (600 images) and validation (400 images) the ROI detection model. The other 2100 captured images were used for training and testing classification OCR failure from manufacturing process model. The model testing was performed in 900 images contained 9 causes (classes) of failures. The proposed model reaches F1 score = 0.94.
Keywords: Classification; EfficientNet; Object detection; Optical character recognition; YOLO